PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DEWAN KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Jasa Sektor Keuangan yang terdaftar di Bursa Efek Indonesia (BEI) Tahun 2013-2015) - Theresia Advenia W. R, 14.05.52.0058; Rizal, Alimuddin (Students' Journal of Accounting and Banking, 2018)
The main goal of every company is to maximize the firm value. The firm value is a reflection of the good or bad performance of the company.Good firm value can be achieved maximally when a company can implement a good corporate governance system. Good corporate governance system mechanisms include managerial ownership, institutional ownership, independent board of commissioners and audit committee. This study aims to examines and analyze the effect of managerial ownership, institutional ownership, independent board commissioners and audit committees to the firm value. The population of this research are financial services companies listed in the Indonesian Stock Exchange period 2013-2015. The study uses secondary data such as financial report period 2013 until 2015, Indonesian Capital Market Directory period 2014 and 2015, also IDX Monthly Statistic period 2016 and obtained as many 20 companies. The technique of data analysis is used multiple regression analysis. The results of this study shows that managerial ownership and audit committees have a negative effect on firm value, independent board of commissioners have a positive effect on firm value, while institusional ownership does not affect with the direction of negative relationship on firm value. Keywords : financial sevices company, managerial ownership, institutional ownership, independent board of commissioners, audit committees, firm value